2008
DOI: 10.1002/fld.1837
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mass lumping on gravity and Rossby waves in 2D finite‐element shallow‐water models

Abstract: SUMMARYThe goal of this study is to evaluate the effect of mass lumping on the dispersion properties of four finiteelement velocity/surface-elevation pairs that are used to approximate the linear shallow-water equations. For each pair, the dispersion relation, obtained using the mass lumping technique, is computed and analysed for both gravity and Rossby waves. The dispersion relations are compared with those obtained for the consistent schemes (without lumping) and the continuous case. The P 0 − P 1 , RT 0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Those are the P 0 − P 1 , P NC 1 − P 0 , and P NC 1 − P 1 pairs. In [17], by diagonalizing the velocity mass matrix, the effect of the so-called mass lumping procedure on inertia-gravity and Rossby waves is analyzed for several other FE pairs.…”
Section: The Finite-element Pairsmentioning
confidence: 99%
“…Those are the P 0 − P 1 , P NC 1 − P 0 , and P NC 1 − P 1 pairs. In [17], by diagonalizing the velocity mass matrix, the effect of the so-called mass lumping procedure on inertia-gravity and Rossby waves is analyzed for several other FE pairs.…”
Section: The Finite-element Pairsmentioning
confidence: 99%
“…Mixed finite‐element methods are the analogue of staggered grids, since they use different finite‐element spaces for velocity and pressure. Many different combinations of finite‐element spaces have been examined in the ocean modelling literature (Le Roux, 2005, 2012; Le Roux et al, 2007, 2009; Danilov et al, 2008; Le Roux and Pouliot, 2008; Rostand and Le Roux, 2008; Comblen et al, 2010; Cotter and Ham, 2011) concentrated on combinations of spaces that have discrete versions of the div−curl and curl−grad identities, just like the C‐grid. In the numerical analysis literature, this is referred to as ‘finite‐element exterior calculus’ (Arnold et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, the multiplicity of the spurious inertial modes x = ±f is not mentioned in [18], although this is crucial to understand the behaviour of such modes, as shown in Section 5. Further, as observed in [5,25,46,58] the shape and configuration of the triangles affect the accuracy of the FE implementation, and the use of equilateral triangles diminishes the directional dependence of the solutions. Numerical experiments have also demonstrated that equilateral triangles are more accurate that right triangles [31].…”
Section: Introductionmentioning
confidence: 95%